Probing and problematizing teacher professional development for inclusion. (2017) - Woodcock, Stuart; Hardy, Ian
Highlights: Formal professional development (PD) has mixed effects on inclusive beliefs. PD in special education has a negative effect upon beliefs in inclusion. Special education teachers did not believe that inclusion was effective for all. Informal PD resulted in more positive beliefs about inclusion than formal PD. There is a need for closer attention to PD for inclusive pedagogies. Abstract: This article explores the nature and extent to which special education professional development (PD) in schools influences teachers' perceptions of inclusion. Drawing upon theorizing of inclusion, including Slee's notion of 'exclusive schooling' and Florian and colleagues' concept of 'inclusive pedagogy', the research employs Saldana's thematic analysis/coding approach to identify key themes from the insights of 120 Canadian elementary and secondary teachers. The results reveal complex, perhaps unanticipated findings, including that increased exposure to current PD in special education appears to have detrimental effects upon teachers' beliefs in, and understandings of inclusion. The research suggests the need for much closer attention to the nature of the PD experiences of teachers to counter more 'exclusive' practices, and to foster more inclusive pedagogies.